2013
DOI: 10.5415/apallergy.2013.3.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric anaphylaxis in a Singaporean children cohort: changing food allergy triggers over time

Abstract: BackgroundWe have noticed changes in paediatric anaphylaxis triggers locally in Singapore.ObjectiveWe aimed to describe the demographic characteristics, clinical features, causative agents and management of children presenting with anaphylaxis.MethodsThis is a retrospective study of Singaporean children presenting with anaphylaxis between January 2005 and December 2009 to a tertiary paediatric hospital.ResultsOne hundred and eight cases of anaphylaxis in 98 children were included. Food was the commonest trigge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 17 publications
8
83
2
2
Order By: Relevance
“…1). The 85 remaining articles [3, 9, 13-21, 24-97] were included in the qualitative analysis (online suppl. Table S1; for all online suppl.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The 85 remaining articles [3, 9, 13-21, 24-97] were included in the qualitative analysis (online suppl. Table S1; for all online suppl.…”
Section: Resultsmentioning
confidence: 99%
“…While the mechanism underlying acetaminophen allergy is not yet fully understood, we can hypothesize that immediate reactions are likely IgE-mediated, as described by de Paramo et al [23]. Studies also report a high risk of hypersensitivity to acetaminophen in patients who experience ibuprofen-induced anaphylaxis [24], so it is important to assess cross-intolerance to acetaminophen in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…The shift in peanut sensitisation patterns in atopic children from fourth to second place was the initial signal of this change. (25)(26)(27) In a recent study by Liew et al, peanut was found to be the top cause of anaphylaxis in a Singapore paediatric emergency centre, (28) whereas it was an absent cause of food anaphylaxis 14 years ago. (29) It is therefore important for medical professionals to watch for this rise in peanut allergy, as it is a frequent cause of fatal anaphylaxis, particularly in adolescents, and is carried into adulthood, with less than 10% outgrowing this allergy.…”
Section: Peanutmentioning
confidence: 99%
“…(14,28) Drugs in children (30%) and insect stings in adults (32%) are the second most common triggers after food.…”
Section: A N a Ph Y L A Xi S In S In G A Po R Ementioning
confidence: 99%
See 1 more Smart Citation